Design proposal of the energy installation system for vehicle’s wind turbine - Rosly, Nurhayati; Mohd, Sofian; Husain, Mohd Hazruwadi; Omar, Zamri; Subari, Zulkhairi; Yunos, Muhamad Zaini (IOP Publishing, 2019)
New inventions is relating to the idea of mounting a wind turbine for power generating system in vehicles. This study will investigate on the existing energy conversion and storage systems used in standard vehicle’s power system.This study involves with a proposed design of a vehicle’s wind turbine system. The energy that has been generated by wind turbine will be stored in the 12 volt battery and will then, be distributed to the entire vehicle for the use of the vehicle components. The optimal design for energy conversion system is created based on the review of the existing energy conversion and storage systems which are used in vehicle’s power system. A simulation study using NI Multisim (National Instrument Software) is conducted on the energy conversion and storage system that. The objectives of this study are to convert a mechanical energy from the blade to electrical energy to generate 12V voltage and to store it in a 12 volt battery. The 12V battery voltage will then be supplied to a high voltage system, up to 200V voltage capacity. From the analysis that has been done, the energy from a turbine has the potential to generate power to car system. The wind energy is possible to integrate with other existing and renewable energy. At this stage, the energy gained does not replace the existing one but it can be considered as a new energy source in the future energy development